Zeolite, Study of Aptitude as a Natural Pozzolan Applied to Structural Concrete - Raggiot, Bárbara Belén; Positieri, María Josefina; Locati, Francisco; Murra, Juan; Marfil, Silvina (Revista de la Construcción. Journal of Construction, 2015)
Nowadays, concrete is one of the most widely used construction materials due to its low price, appropriate mechanic characteristics and durability. Also, due to its ease to adopt diverse forms and sizes (Najimi et al., 2012). Owing to the importance in the use of concrete as a structural material and to its impact in the environment as a consumer of great quantities of natural resources and emitter of CO2 in the concrete industry, it is necessary to develop, from the science of materials, mixtures that support the growth of the construction industry and that consider the environment. Therefore, it becomes necessary to develop energetically efficient materials. A natural zeolite was studied as a material with potential pozzolanic activity and as partial replacement in different percentages of Portland cement in structural concrete. The results of the mechanic trials in concrete samples prove the feasibility of using this element as pozzolanic material.